Principles of Social Reconstruction - Russell, Bertrand (London Unwin Paperbacks, 1994)
Originally entitled Why Men Figh, this work is generally seen as the fullest expression of Russell's political philosophy. The ideas laid out here greatly contributed to Russell's fame as a social critic and anti-war activist.
Include Index
Keywords: Social problems -- War -- Property